Pengaruh Kepemimpinan Kepala Sekolah dan Lingkungan Kerja Terhadap Etos Kerja Guru di SDN 006 Pompa Air - Nuryati Nuryati (Yayasan Sembilan Pemuda Indonesia, 2026)
Based on the results of the analysis that has been done, this study uses a quantitative approach with a causal associative research type, because it aims to determine the influence between two independent variables (principal leadership and work environment) on the dependent variable (teacher work ethic). This approach is used to test the hypothesis through the collection of quantitative data that is analyzed statistically. The sample in this study were teachers who teach at SDN 006 Pompa Air, the number of samples needed was 23 teachers. The study concluded that effective principal leadership and good performance play an important role in improving the work ethic of teachers at SDN 006 Pompa Air. The principal's leadership style, appropriate managerial strategies, and the ability to create a positive work environment are some of the key factors that support the improvement of work ethic among teachers at SDN 006 Pompa Air. To improve teacher work ethic, teachers can develop professional and personal competencies, increase discipline and responsibility, apply positive work ethic habits, participate in academic supervision and training, increase work motivation and discipline, build good interpersonal relationships at SDN 006 Pompa Air.